2014
DOI: 10.4161/15592294.2014.971626
|View full text |Cite
|
Sign up to set email alerts
|

Methylation status ofIGFBP-3as a useful clinical tool for deciding on a concomitant radiotherapy

Abstract: The methylation status of the IGFBP-3 gene is strongly associated with cisplatin sensitivity in patients with non-small cell lung cancer (NSCLC). In this study, we found in vitro evidence that linked the presence of an unmethylated promoter with poor response to radiation. Our data also indicate that radiation might sensitize chemotherapy-resistant cells by reactivating IGFBP-3-expression through promoter demethylation, inactivating the PI3K/AKT pathway. We also explored the IGFBP-3 methylation effect on overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The DNA from H23S/R, H460S/R, A2780S/R, and OVCAR3S/R was isolated as described [ 48 ] and sent to the National Centre for Genome Analysis [ Centro Nacional de Análisis Genómico (CNAG)] for WGBS (GSE109317). Briefly, 2 µg of genomic DNA was mixed with unmethylated DNA from lambda phage in a proportion of 5 ng for each µg of genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The DNA from H23S/R, H460S/R, A2780S/R, and OVCAR3S/R was isolated as described [ 48 ] and sent to the National Centre for Genome Analysis [ Centro Nacional de Análisis Genómico (CNAG)] for WGBS (GSE109317). Briefly, 2 µg of genomic DNA was mixed with unmethylated DNA from lambda phage in a proportion of 5 ng for each µg of genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The commercial kit for detecting methylation at IGFBP-3 gene is under development, and its use is directed toward the identification of NSCLC patients who could benefit more from concomitant chemotherapy-radiotherapy. 27,50,51 Lung cancer. Lung cancer is the worldwide leader in tumor-related deaths.…”
Section: Translational Applications Of Methylome Studies In Cancermentioning
confidence: 99%
“…These data suggested that more advanced disease was associated with increased incidence of IGFBP-3 promoter methylation (Chang et al 2004). (Pernia et al 2014) using 40 NSCLC patients who were treated with chemotherapy with or without radiotherapy determined that patients with an unmethylated IGFBP-3 promoter would do better with chemotherapy alone as opposed to the combination therapy (Pernia et al 2014). …”
Section: Evidence For Epigenetic Alteration Of Igfbp-3 In Cancermentioning
confidence: 99%